PENGARUH KOMPOSISI PENDUDUK TERHADAP KESEJAHTERAAN MASYARAKAT DI INDONESIA - CHARISMA KURIATA GINTING (JURNAL ILMIAH SIMANTEK, 2023)
Attention and studies on population dynamics have focused on population growth. Therefore, the policies and programs developed and implemented are targeted at efforts to reduce the rate of population growth. Looking closely, based on Malthus' theory, the population is not the root of the problem, but the natural resources supporting the life of the population whose availability is limited become a constraint factor. Karl Marx's theory states that a larger population will lead to income distribution problems due to the confounding factor of limited available employment. A more specific variable is needed that can represent the confounding factor in analyzing population dynamics and its effect on HDI (Human Development Index). The HDI variable is used as a proxy for welfare as a concept initiated and used by the United Nations (UN) today. A variable that can accommodate the above-mentioned confounding factors in the discussion of population dynamics is to create a variable that contains elements of population size, density and dependency ratio. Density is a representation of limited resources, where area is a proxy for natural resources. For this reason, a variable is synthesized that integrates the confounding elements by indexing the population density and dependency ratio indicators into a new index called the population composition index. The regression results show that Population Composition has a positive and significant effect on Community Welfare with a coefficient value of 0.527296. Every one percent increase in Population Composition will increase Community Welfare by 0.527296 percent. The regression results also explain that the influence of the density variable is more dominant in influencing community welfare than the population dependency ratio.